On the importance of hygienic measures in control of airborne infectious transmitted by air - Stankov, Srđan (Srpski medicinski časopis Lekarske komore, 2021)
Infectious diseases have existed in the form of epidemics throughout the history of mankind and pathogenic microorganisms have long been held responsible for their occurence. However, the so-called biological agents of acute infectious diseases are not their real causes, but only catalysts of already existing pathological processes. Hence the extreme variability of both the location and intensity of pathological processes with the same biological causative agent in different individuals of the host species. Pathogenicity and virulence of microorganisms are not their inherent and invariant properties, but are merely the result of pathogenicity of inanimate environmental factors that act on the host, and which usually remain out of the focus of medical research.The question of main practical importance, how to prevent the appearance of infectious diseases, is given to us by history. In the past, many hygienic measures were sufficient to reduce most infectious diseases to a negligible extent. So far, society has done a lot on hygienic standards of solid and liquid matter in human environment. However, care of the hygiene of the atmosphere has remained quite undeveloped and neglected. Today, the atmosphere is constantly and systematically polluted with specific gases, vapors as well as particles. The direct result of this state of development of hygienic practice is that today the only type of epidemic that affects the general population are epidemics that spread through the atmosphere, respiratory epidemics. In order to permanently eliminate further possibility of respiratory epidemics, there is a necessity to introduce permanent and systematic measures to maintain the hygiene of the atmosphere of human settlements.